1993
DOI: 10.1084/jem.178.4.1419
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a cross-reactive idiotope on human immunoglobulins utilizing the VH4-21 gene segment.

Abstract: SummaryThe anti-idiotypic (anti-Id) antibody (Ab) 9G4 binds a cross-reactive idiotope (CRI) present in a select group of human autoantibodies. This Id has been localized to the portion of immunoglobulin (Ig) heavy (H) chains encoded by the V,4-21 gene segment, a member of the human V.4 family. This gene segment is utilized by essentially all cold agglutinin (CA) Abs with I/i specificity isolated from patients with CA disease stemming from chronic lymphoproliferative disorders. In this study, mutational analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 51 publications
2
56
0
Order By: Relevance
“…This gene segment is of interest, since it encodes an antibody that recognizes autologous determinants on red blood cells, the I/i antigens (39). Furthermore, it has been shown that a monoclonal antiidiotype antibody, 9G4, recognizes a conformation-dependent idiotype that is highly associated with the 4-34/DP-63 gene segment (40). In the current study, 4-34/DP-63 was the third most commonly used V H 4 family member, but its frequency in the productive or nonproductive repertoires of peripheral blood B cells was not significantly different than that predicted from random usage.…”
Section: Discussionmentioning
confidence: 75%
“…This gene segment is of interest, since it encodes an antibody that recognizes autologous determinants on red blood cells, the I/i antigens (39). Furthermore, it has been shown that a monoclonal antiidiotype antibody, 9G4, recognizes a conformation-dependent idiotype that is highly associated with the 4-34/DP-63 gene segment (40). In the current study, 4-34/DP-63 was the third most commonly used V H 4 family member, but its frequency in the productive or nonproductive repertoires of peripheral blood B cells was not significantly different than that predicted from random usage.…”
Section: Discussionmentioning
confidence: 75%
“…This member of the V H 4 gene family is extensively used for B cell Ag receptors with specificity for RBC and B lymphocyte carbohydrate Ags (65)(66)(67)(68)(69)(70). Ongoing studies will reveal whether similar patterns develop when mice are transplanted with adult human stem cells and this information may bear on the issue of what drives CD5 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the gene V H 4 -34 frequently used in the clonally unrelated CD27 high cells analyzed here has been reported previously to be involved in the formation of anti-dsDNA Abs in SLE patients (40 -42) and to be expanded in patients with disease activity (41). This V H 4 gene encodes cold agglutinins (43)(44)(45). It was also frequently used in immune responses of infectious mononucleosis (41,46).…”
Section: Discussionmentioning
confidence: 99%